Students’ well-being development in the classroom: a mixed-method study - Rahmat Aziz; Mulyadi Mulyadi; Muhammad Samsul Hadi; Esa Nur Wahyuni; Rubaidi Rubaidi (Institute of Advanced Engineering and Science, 2024)
Students’ well-being is a fundamental goal in education. The school has a strategic role in developing students’ well-being. This study elaborates on teachers’ classroom activities to develop students’ well-being. The research employed a mixed-method sequential explanatory approach. There were 1,100 students from 11 junior high schools in East Java Province, Indonesia, provided quantitative data. Four teachers provided qualitative data. Descriptive and regression analysis techniques were used for analyzing quantitative data, while thematic analysis was used for analyzing qualitative data. The results show that the hypothesis is accepted. It means that classroom climate affects students’ well-being. The findings also showed four teacher strategies for developing students’ well-being, namely: creating harmonious relationships with students, developing student potential, helping students with difficulties, and creating rules to make students comfortable being in school. The ability of teachers to manage learning in the classroom affects the high level of students’ well-being. The results have implications for the development of students’ well-being through positive teachers teaching.